High-Transmission Biomimetics Structural Surfaces Produced via Ultrafast Laser Manufacturing - Rui-Zhe Leng; Bi Yun; Zhi-Hao Chen; Chen Chai; Wei-Wei Xu; Yan-Hao Yu; Lei Wang (Biomimetics, 2023)
Inspired by periodically aligned micro/nanostructures on biological surfaces, researchers have been fabricating biomimetic structures with superior performance. As a promising and versatile tool, an ultrafast laser combined with other forms of processing technology has been utilized to manufacture functional structures, e.g., the biomimetic subwavelength structures to restrain the surface Fresnel reflectance. In this review paper, we interpret the biomimetic mechanism of antireflective subwavelength structures (ARSSs) for high-transmission windows. Recent advances in the fabrication of ARSSs with an ultrafast laser are summarized and introduced. The limitations and challenges of laser processing technology are discussed, and the future prospects for advancement are outlined, too.